ПЕВЦИ: (АУТОПОЕТИЧКИ) РОМАН БОРИСАВА СТАНКОВИЋА О САМОУКИДАЊУ1 (Philological Studies, 2014)
This paper analyses the unfinished novel Pevci (Singers), written by Borisav Stanković, one of the most important Serbian writers of the XX century. Following a short review of the former approaches to this work and a critical reassessment of the novel’s editors’ proceedings, the article offers a semantic analysis of the text. The hero’s attitude towards the norms of patriarchal culture, i.e. the difficulties in establishing a masculine identity, is emphasized as a dominant trait of this novel. Related to this is the protagonist’s feeling of shame and a need for self-annihilation. The paper also discusses poetic similarities with other works of the same author, particularly the novel Gazda Mladen (Master Mladen) and the short story “Oni” (“Them”).
Keywords: Borisav Stanković, Pevci (Singers), poetics, norms of patriarchal culture, masculinity, feeling of fear, unworthiness in regard to one’s gender role, self-isolation, self-annihilation